Transvenous lead extraction in patients with cardiac resynchronization therapy devices is not associated with increased 30-day mortality. Issue 6 (24th December 2018) - Gould, Justin; Klis, Magdalena; Porter, Bradley; Sieniewicz, Benjamin J; Sidhu, Baldeep S; Claridge, Simon; Williams, Steven E; Shetty, Anoop; O'Neill, Mark; Gill, Jaswinder; Rinaldi, Christopher A
Abstract: Aims: Transvenous lead extraction (TLE) may be necessary due to system infection/erosion or lead malfunction. Cardiac resynchronization therapy (CRT) patients undergoing TLE may be at greater risk due to increased comorbidities. We examined whether patients with CRT systems undergoing TLE had more comorbidities and higher 30-day mortality than those with non-CRT devices. Methods and results: All TLEs between October 2000 and December 2016 were prospectively collected. During this period 925 TLEs occurred (CRT group 231, non-CRT group 694). Cardiac resynchronization therapy patients were older (68.1 ± 10.8 years vs. 64.3 ± 16.1 years, P = 0.024); more likely male (85.7% vs. 69%, P < 0.001); had lower mean left ventricular ejection fraction (34.1 ± 12.7% vs. 48.3 ± 12.9%, P < 0.001); had higher prevalence of renal impairment (33.8% vs. 13.7%, P < 0.001) and were more likely to have ≥2 comorbidities (84% vs. 40.1%, P < 0.001). Mean lead dwell time was lower in the CRT group (5.6 ± 5.5 years vs. 7.6 ± 7.1 years, P = 0.002). There was no significant difference in all-cause 30-day mortality rates between CRT (3.0%, n = 7) and non-CRT patients (2.0%, n = 14) ( P = 0.443). The majority of deaths in both groups were due to sepsis. Univariate and multivariate analysis showed age, renal impairment and sepsis were associated with increased risk of 30-day mortality. Transvenous lead extraction of a CRT system did not predict 30-day mortality. Conclusion: Transvenous lead extraction in CRT patients was not associated with increased 30-day mortality when compared with non-CRT patients. Age, renal impairment and sepsis were independent predictors of 30-day mortality. Sepsis was the main cause of 30-day mortality.